Dataset used for "Improved Understanding of Multicentury Greenland Ice Sheet Response to Strong Warming in the Coupled CESM2‐CISM2 with Regional Grid Refinement" - Herrington, Adam; Ziqi, Yin (Zenodo, 2024)
Annual or summer (JJA) mean variables from two CESM2-CISM2 simulations: 'F09' uses the f09 grid for the atmosphere and land components, 'ARCTIC' uses the variable-resolution arctic grid. Three periods - piControl, 1pctCO2 and 4xext are included. CAM variables: CLDTOT, PHIS, PS, T, TGCLDLWP, TREFHT, Z3 CLM variables: EFLX_LH_TOT, FGR, FIRA, FLDS, FSDS, FSH, FSM, FSR, PCT_LANDUNIT, QFLX_EVAP_TOT, QICE_MELT, QRUNOFF, QSNOMELT, RAIN, SNOW CISM variables: iarea, ice_sheet_mask, ivol, thk, total_bmb_flux, total_calving_flux, total_smb_flux POP variables: MOC CICE variables: aice, hi